Empirical Analysis of the Impact of Exports and Imports on Inflation in Indonesia - Rizqon Halal Syah Aji; Rizki Dito Subekti; Chaerul Akbar (Research Synergy Foundation, 2025)
This study aims to analyze the impact of exports and imports on inflation in Indonesia. The analysis considers macroeconomic variables such as money supply, interest rates, exchange rates, and foreign exchange reserves during 2014-2023. Studying inflation in Indonesia is crucial because it affects economic stability, purchasing power, and policy effectiveness. The Error Correction Model (ECM) is used, which allows for the analysis of long-term and short-term dynamics. The unit root test for stationery and Johansen’s co-integration tests were carried out to examine long-term relationships. The multicollinearity, autocorrelation, and heteroscedasticity tests are applied to the Best Linear Unbiased Estimators (BLUE) assumption. The estimation results indicate that exports significantly affect inflation, whereas imports do not. Foreign exchange reserves have a negative and significant impact, whereas the amount of money in circulation is insignificant. This emphasizes the importance of adaptive monetary policy, a more competitive export strategy, and more flexible management of foreign exchange reserves to maintain inflation stability in Indonesia. Bank Indonesia must consider the persistence of inflation when determining its interest rate policy and controlling liquidity so that its impact on the economy can be more controlled.